Genetic and phenotypic characteristics of Clostridium (Clostridioides) difficile from canine, bovine, and pediatric populations. (April 2022) - Redding, L.E.; Tu, V.; Abbas, A.; Alvarez, M.; Zackular, J.P.; Gu, C.; Bushman, F.D.; Kelly, D.J.; Barnhart, D.; Lee, J.J.; Bittinger, K.L.
Abstract: Objectives: Carriage of Clostridioides difficile by different species of animals has led to speculation that animals could represent a reservoir of this pathogen for human infections. The objective of this study was to compare C. difficile isolates from humans, dogs, and cattle from a restricted geographic area. Methods: C. difficile isolates from 36 dogs and 15 dairy calves underwent whole genome sequencing, and phenotypic assays assessing growth and virulence were performed. Genomes of animal-derived isolates were compared to 29 genomes of isolates from a pediatric population as well as 44 reference genomes. Results: Growth rates and relative cytotoxicity of isolates were significantly higher and lower, respectively, in bovine-derived isolates compared to pediatric- and canine-derived isolates. Analysis of core genes showed clustering by host species, though in a few cases, human strains co-clustered with canine or bovine strains, suggesting possible interspecies transmission. Geographic differences (e.g., farm, litter) were small compared to differences between species. In an analysis of accessory genes, the total number of genes in each genome varied between host species, with 6.7% of functional orthologs differentially present/absent between host species and bovine-derived strains having the lowest number of genes. Canine-derived isolates were most likely to be non-toxigenic and more likely to carry phages. A targeted study of episomes identified in local pediatric strains showed sharing of a methicillin-resistance plasmid with dogs, and historic sharing of a wide range of episomes across hosts. Bovine-derived isolates harbored the widest variety of antibiotic-resistance genes, followed by canine Conclusions: While C. difficile isolates mostly clustered by host species, occasional co-clustering of canine and pediatric-derived isolates suggests the possibility of interspecies transmission. The presence of a pool of resistance genes in animal-derived isolates with the potential to appear in humans given sufficient pressure from antibiotic use warrants concern. Highlights: C difficile isolates from pediatric, canine and bovine populations phylogenetically clustered by host species. Occasional co-clustering of isolates suggests the possibility of interspecies circulation of C. difficile. Animal-derived strains possessed antimicrobial resistance genes not found in human-derived strains.